Regional developments: Africa [in 2025 GFPR] - Ulimwengu, John M.; Omamo, Steven Were; Badiane, Ousmane; Benin, Samuel (International Food Policy Research Institute, 2025)
Africa’s food systems have undergone significant transformations over the past four decades, with notable improvements in agricultural productivity and food security, but persistent challenges remain. This chapter examines how Africa’s agrifood policy landscape has evolved over time in response to complex challenges, including food insecurity, climate change, and socioeconomic disparities. It explores how IFPRI and other international organizations have offered research-based solutions to Africa’s development challenges, as well as underscoring the necessity of systemic, inclusive, and evidence-based approaches to address the agrifood system challenges projected for 2050.